Biodiversity spongia in the marine waters from Hon Me (Thanh Hoa) to Hai Van - Son Tra (Thua Thien Hue) - Do, Cong Thung (Vietnam Journal of Marine Science and Technology, 2022)
The study of Sponge biodiversity in the waters from Hon Me (Thanh Hoa) to Hai Van - Son Tra (Thua Thien Hue) was conducted in 2017, 2018, and 2022 in 5 regions with 43 sampling points. Seventy-four Sponge species belonging to 44 genera, 31 families, 15 orders were identified. Con Co island sampling point offshore Quang Tri is the place where the Sponge species are most diversified and abundant (54 out of 74 species), followed by Hai Van - Son Tra (26 species), rock reefs near Nhat Le, Quang Binh, with 25 species, Hon Me (Thanh Hoa) with 24 species and the lowest species range in the reef area near Vinh Moc, Quang Tri, with 22 species. The Sponges occur at a depth of 3–10 m, with maximum concentration at 5 m depth. The distribution varies based on the nature of the substrate: coral-reef bedrock displays the highest number of species (55); on the original reef-rock substrate 35 species have been counted; on sandy bottom with coral debris, the number of detected species decreases to 23 species. On the dead-coral substrate, there were 20 species detected; on the mixed and and rocky bottom the sponge assemblage is represented by only 12 species, and on mud, sandy mud and fine sand, the species range from from 0 to 4. The biomass varies from 0.9 kg/m2 to 2.5 kg/m2, the highest being on Con Co island, with an average of 2.5 kg/m2 and the lowest in Vinh Moc, Quang Tri Province with 0.9 kg/m2. Sponges proved to be the source of several medicinal components. It is possible to forecast three areas that are likely to become the potential source of medicinal products from sponges in our country: the Con Co medicinal yard, the Hai Van - Son Cha medicinal yard, and the third important marine medicinal yard in the Hon Me archipelago, Thanh Hoa.